MODEL INDUKTIF KATA BERGAMBAR ANIMASI TERHADAP KEMAMPUAN MENULIS PERMULAAN ANAK TUNARUNGU DI SLB - INDRA PRATIWI, SEVI (Jurnal Pendidikan Khusus, 2016)
Abstract   The purpose of this research was to observe whether there was influence of using inductive model of picturing animation words toward beginning writing ability to hearing impairment children or not. In the academic domain, the hearing impairment children had difficulty in speech skill, the skill, for example, disturbance in writing skill which was caused by the low vocabulary mastered by the children. The writing skill could be improved using inductive model of picturing animation words. This learning model was given with the purpose to enhance writing skill to hearing impairment students through the performance of animation picture given in learning class in the form of moving picture accompanied words for each picture object. To avoid the problem in writing intervention was given first through beginning writing with the purpose to train and customize the children scratching. The research used quantitative approach. The research kind was pre-experiment. The design used was one group pretest-posttest. The data analysis was statistic non parametric using sign test formula. The collection method used test and documentation. The time applied was 8 times meeting with 6 times intervention. The subject was 6 hearing impairment children. The instrument of this research was syllabus and plan of learning implementation equipped by material. In the research result, there were some differences i.e. in the theory and the research before the picture was given using printed picture whereas in this research the picture was given in the form of animation. This research which had been done indicated that there was score enhancement of beginning writing skill to six hearing impairment children, the average value of pretest was 45,49 and the average value of posttest was 86,51. From the research result which was then analyzed using sign test formula with two sides test it was obtained that the value of Zh = 2,05 > Zt = 1,96 to significant level 5% so that it could be concluded that there was influence of inductive model of picturing animation words toward beginning writing skill to hearing impairment children in SLB PGRI Bandung Tulungagung.   Keywords: Inductive Model of Picturing Animation Words, Beginning Writing Skill